Competency and Its Many Meanings - Zubin Austin (MDPI AG, 2019)
Competency and competency assessment are central to much of professional education, regulation, and practice. In the name of safe and effective professional practice, elaborate competency education and competency assessment systems have evolved, and consume significant time, energy, and financial resources. This paper will review the evolution of competing competency discourses in pharmacy and discuss implications of these approaches on professional practice, with particular emphasis on understanding the consequences of outsized focus on competency at the expense of other potential lenses for understanding professional practice.